The Perfect Colonizer: Understanding Alcoholism and its Treatments in Native America through Humanistic Inquiry - McPherson, Kevin; Wakefield, Peter (Journal of Student Research, 2015)
According to the Indian Health Services, the rate of alcoholism among Native Americans is six times higher than the U.S. average, while one in every ten Native American deaths are a result of some alcohol related cause. Even before colonization, alcohol and its consumption were depicted in many trading exchanges between early settlers and Native Americans. In present day, alcohol has presented itself as a problem to Native Americans: commonly known by many as the “perfect colonizer” one which “has no conscience [and] shows no remorse for the modern-day holocaust for which it has caused.” The current study seeks to answer the following questions: with Native Americans being intimately tied to alcohol via history, stigma, and disease prevalence, why do Native Americans hold the belief that alcohol is the “perfect colonizer”? And, on the auxiliary, why are modern treatments (e.g., AA’s 12 Step Process) ineffective in treating alcoholism in Native populations? Through various modes of humanistic inquiry, probing philosophy, film, and modern-day intervention techniques, we have found that the model to understanding alcoholism is illustrated via a three-column system, holding up the definition of alcoholism as the “perfect colonizer.”